The cinema of Louis Malle : transatlantic auteur - Met, Philippe (Directors' cuts., 2018)
A pioneer of the French New Wave, Louis Malle went on to an acclaimed transatlantic career. This collection of essays reassesses his eclectic and subversive oeuvre to redress the critical neglect it has suffered. The volume features contributions from playwright John Guare and filmmakers Volker Schlöndorff and Wes Anderson.